Gender Differences and Learner Satisfaction: An evaluation of E-‎Learning Systems at Umm A-Qura University - Ahmed Alharthi; Hanaa Yamani; Waleed Elsigini (Journal of Distance Learning and Open Learning, 2021)
This research aims to define the students' satisfaction level at Umm Al-Qura ‎University with the e-learning systems (Blackboard & D2L), in addition, it ‎investigates whether there are differences in the evaluation of Umm Al-Qura ‎University students for e-learning systems (Blackboard & D2L) due to the gender ‎variable (Male/ Female).‎ To achieve these goals, a descriptive analysis methodology used in this research, ‎the sample consisted of (513) students, (174) male, and (339) female at Umm Al-Qura ‎University in the the academic year 2019/2020. The sample were asked to complete a ‎‎5-point likert scale questionnaire to collect the required data. Validity and reliability of ‎the questionnaire were guaranteed. ‎ The results revealed that students are highly satisfied with the both of e-learning ‎systems (Blackboard & D2L). There is no statistically significant difference between ‎the average scores of males and females in the evaluation of the e-learning system ‎‎(Blackboard). There is a statistically significant difference between the mean scores of ‎males and females in the D2L system evaluation in favor of females